Permainan Plasticine sebagai Media Konseling Anak Pelaku Bullying Usia 5-7 Tahun - Fia Nurul Fauziah (PEDAGOGIKA, 2021)
The main factor for bullies to act aggressively and to harass others is the inability to define and express emotions. The importance of positive reinforcement in the process of child development and growth, especially in introducing the meaning of emotions and how to express emotions well. This study aims to elaborate several theoretical foundations regarding bullying, emotions and the implementation of child counseling using plasticine media. The research method used is literature study method. Methods of data analysis using content analysis methods. The results of this study are the elaboration of the theoretical basis and implementation of child counseling using plasticine as a whole, which includes: 1) managing emotions as a way to reduce aggressiveness, 2) implementing child counseling in cases of bullying, 3) counseling stages using plasticine games, 4) advantages of plasticine media , 5) measurement of counseling achievement parameters using plasticine media.